Cytotoxicity Activity of Crude Extracts of Leum Phua Khaow-Mak (Oryza sativa L. variety Leum Phua) against Fibroblast Cell - Wattanuruk, Duangduan; Phasuk, Sasamol; Nilsang, Poonyanuch; Takolpuckdee, Pannraphat (Journal of Food Health and Bioenvironmental Science, 2023)
Leum Phua Khaow-Mak is a fermented food, which provides high amounts of nutrients and antioxidant bioactive compounds such as phenolic compounds. Leum Phua Khaow-Mak extract compounds also have potential for applications in cosmetics and function food formulations. The objective of this research was to investigate cytotoxic activity of crude extracts from Leum Phua Khaow-Mak to human dermal fibroblast cells using sulforhodamine B (SRB) colorimetric assay method. Leum Phua glutinous rice (Oryza sativa L. variety Leum Phua) was fermented with a starter (Look Pang) at room temperature for 5 days. Fermented rice samples were extracted with 95% ethanol for 24 hours. The solvent was evaporated at 45°C to obtain dried crude extracts. The antioxidant capacity of crude extracts was determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging. Butylated hydroxytoluene (BHT) was used as a standard antioxidant. The EC50 value of the extract was 0.367 mg/ml, as similar to that of BHT (EC50 = 0.239 mg/ml). A dried sample was dissolved with 10% (v/v) dimethyl sulfoxide (DMSO) in the cell culture media. Cytotoxic activity of crude extracts to human dermal fibroblast cell was evaluated. The cell cultures were fixed in ice-cold 40% trichloroacetic acid (TCA) and were dyed using 0.05% sulforhodamine B for 30 min. Sodium lauryl sulfate was used as the positive control. The optical density was measured at 510 nm in a microplate reader. The percentage of viability of human dermal fibroblast cell were calculated and compared with sodium lauryl sulfate. The results showed that the concentrations of crude extracts from Leum Phua Khaow-Mak at 0.0001-1.0 mg/ml have the percentage of viability at 105.17-102.29 respectively. The percentage of viability of sodium lauryl sulfate at 0.0001-1.0 mg/ml have the percentage viability at 99.43-4.91 respectively. The percentage of viability at the concentrations of 0.1 and 1.0 mg/ml were low. These obtained results indicated that the concentrations of crude extracts from Leum Phua Khaow-Mak in the range between 0.0001 and 1 mg/ml were non-toxic to human dermal fibroblast cells.